A novel long non-coding RNA CYP4B1-PS1-001 regulates proliferation and fibrosis in diabetic nephropathy. (5th May 2016) - Wang, Min; Wang, Suyu; Yao, Di; Yan, Qin; Lu, Weiping
Abstract: Diabetic nephropathy is an important microvascular complication of diabetes, and the incidence of end-stage renal disease caused by it are rising annually. Long non-coding RNAs (lncRNAs) are widely regarded to associate with the occurrence and development of various diseases; however, the relationship between lncRNAs and diabetic nephropathy remains largely unknown. This work studied the effect of lncRNAs on diabetic nephropathy pathogenesis. LncRNA microarrays were initially used to detect lncRNAs with altered expression in three cases of kidney tissue from db/db mice with diabetic nephropathy. LncRNAs with differential expression (>2-fold) could be considered candidates. Particularly, CYP4B1-PS1-001 was significantly downregulated in response to early diabetic nephropathy in vitro and in vivo, while overexpression of CYP4B1-PS1-001 inhibited proliferation and fibrosis of mesangial cells. Overall, our data indicate the potential role of CYP4B1-PS1-001 in the proliferation and fibrosis of mice mesangial cells as the prominent features during early stage of diabetic nephropathy, which extend the relationship between lncRNAs and diabetic nephropathy, and may provide a potential therapeutic target and molecular biomarker for the disease. Highlights: 1018 lncRNAs were differentially expressed in kidney tissue from db/db mice with diabetic nephropathy. CYP4B1-PS1-001 was significantly downregulated in response to early diabetic nephropathy. Overexpression of CYP4B1-PS1-001 inhibited proliferation and fibrosis of mesangial cells.